Polycentric Systems of Governance: A Theoretical Model for the Commons - and Carlisle, Keith; Gruby, Rebecca L. (Policy Studies Journal, 2019)
Polycentricity is a fundamental concept in commons scholarship that connotes a complex form of governance with multiple centers of semiautonomous decision making. If the decision-making centers take each other into account in competitive and cooperative relationships and have recourse to conflict resolution mechanisms, they may be regarded as a polycentric governance system. In the context of natural resource governance, commons scholars have ascribed a number of advantages to polycentric governance systems, most notably enhanced adaptive capacity, provision of good institutional fit for natural resource systems, and mitigation of risk on account of redundant governance actors and institutions. Despite the popularity of the concept, systematic development of polycentricity, including its posited advantages, is lacking in the commons literature. To build greater clarity and specificity around the concept, we develop a theoretical model of a polycentric governance system with a focus on the features necessary or conducive for achieving the functioning predicted by commons scholars. The model is comprised of attributes, which constitute the definitional elements, and enabling conditions, which specify additional institutional features for achieving functionality in the commons. The model we propose takes the concept a step further toward specificity without sacrificing the generality necessary for contextual application and further development.